Critical analysis of self-doping and water-soluble n-type organic semiconductors: structures and mechanisms. Issue 23 (24th May 2022) - Cowen, Lewis M.; Gilhooly-Finn, Peter A.; Giovannitti, Alexander; LeCroy, Garrett; Demetriou, Harry; Neal, William; Dong, Yifan; Westwood, Megan; Luong, Sally; Fenwick, Oliver; Salleo, Alberto; Heutz, Sandrine; et al.
Abstract : The structure of a self-doping naphthalenetetracarboxylic diimide was found to be the product of unexpected chemical reactions. The effect a mixed chemical composition has on the doped film morphology and electronic performance is also reported. Abstract : Self-doping organic semiconductors provide a promising route to avoid instabilities and morphological issues associated with molecular n-type dopants. Structural characterization of a naphthalenetetracarboxylic diimide (NDI) semiconductor covalently bound to an ammonium hydroxide group is presented. The dopant precursor was found to be the product of an unexpected base catalyzed hydrolysis, which was reversible. The reversible hydrolysis had profound consequences on the chemical composition, morphology, and electronic performance of the doped films. In addition, we investigated the degradation mechanism of the quaternary ammonium group and the subsequent doping of NDI. These findings reveal that the products of more than one chemical reaction during processing of films must be considered when utilizing this promising class of water-soluble semiconductors.